الإدارة الإلكترونية وأثر تطبيقها على جودة الخدمات الجامعية بجامعة المدية - من وجهة نظر طلبة المالية والمحاسبة - - عبابه علي . بصاشي هدى . عليش فطيمة . (جامعة الوادي - University of Eloued, 2022)
تهدف الدراسة إلى معرفة أثر تطبيق الإدارة الإلكترونية على جودة الخدمات الجامعية وذلك من خلال معرفة طبيعة العلاقة ما بين الإدارة الإلكترونية وجودة الخدمات الجامعية من وجهة نظر طلبة المالية والمحاسبة بجامعة المدية، ولتحقيق أهداف هذه الدراسة فقد تم تصميم استبانة وتوزيعها على أفراد عينة الدراسة والبالغ عددهم (50) مفردة، ولقد تم استخدام الرزمة الإحصائية للعلوم الاجتماعية (SPSS) لتحليل البيانات بحيث توصلت الدراسة إلى انه يوجد اثر ذو دلالة إحصائية لمتغير الإدارة الإلكترونية على جودة الخدمات الجامعية عند مستوى 0.05 إذا بلغ (t=5.704) بمستوى دلالة (0.000)، وتشير قيمة معامل الارتباط (R) إلى أن قوة العلاقة بين المتغيرين السابقين هي (0.750). Abstract: The study aims to determine the impact of the application of electronic administration on the quality of University services through knowledge of the nature of the relationship between management of electronic and university service quality, from the viewpoint of the students of Finance and accounting the University of Medea, in order to achieve the objectives of the study a questionnaire was designed and distribute it to the members of the study sample whose number is (50), by using the statistical package for social sciences (SPSS) to data analysis, the study finds there is a statistically significant effect of a variable electronic management on the quality of University services at 0.05 level if (t = 5.704) level indication (0.000) and Value of the correlation coefficient (R) that strength of relationship between former variables are (0.750(.
Electronic administration and the impact of its application on the quality of university services at the University of Medea - From the point of view of students of finance and accounting 1
Keywords: الإدارة الإلكترونية ; جودة الخدمات الجامعية ; جامعة المدية